2013
DOI: 10.1007/s10517-013-1980-0
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypical Characteristics of Peripheral Blood Monocytes in Normal Pregnancy and Gestosis

Abstract: Monocyte migration from the peripheral blood to the uterine decidual tissue is essential for the regulation of placental development. We evaluated the phenotypical changes in the peripheral blood monocytes in pregnant women. The peripheral blood counts of monocytes expressing CD11b, CD47, and integrin β7 were elevated in women with normal gestation in comparison with nonpregnant women; the intensity of CD62P, CD11b, CD11c, CD29, CD31, and CD54 expression was higher in pregnancy. The counts of monocytes express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Nevertheless, this number was not different from the number of endothelial-derived microparticles in women with preeclampsia. 40 The number of microparticles formed by NK-cells was higher in women with normal pregnancy than in nonpregnant women and women with preeclampsia. Women with preeclampsia had the increased number of microparticles with a phenotype typical for neutrophils and monocytes, compared to women with normal pregnancy.…”
Section: Accepted Manuscriptmentioning
confidence: 93%
See 3 more Smart Citations
“…Nevertheless, this number was not different from the number of endothelial-derived microparticles in women with preeclampsia. 40 The number of microparticles formed by NK-cells was higher in women with normal pregnancy than in nonpregnant women and women with preeclampsia. Women with preeclampsia had the increased number of microparticles with a phenotype typical for neutrophils and monocytes, compared to women with normal pregnancy.…”
Section: Accepted Manuscriptmentioning
confidence: 93%
“…preeclampsia can be based on the above mentioned differences in the amount and the composition of microparticles. 40,41 In this way, it was indicated that the total number of peripheral blood microparticles of women with normal pregnancy was significantly greater than the total number of peripheral blood microparticles of healthy nonpregnant women. No differences were noticed between the groups of pregnant women with preeclampsia and women without this disease.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
See 2 more Smart Citations